Penggunaan Media Puzzle Untuk Meningkatkan Hasil Belajar Mengidentifikasi Sifat-Sifat Bangun Datar Di Sekolah Dasar - Nur Syafi’ah Khotim (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2016)
The researcher did an repaired action with using a puzzle media on identify two dimention space subject. Thus, the study aimed to describe the use of Puzzle as a medium to improve the score of mathematics in the material of identification of the characteristics of two dimensien space media in the fifth grader of an elementary school and to identify the difficulties in the learning process. This study was a classroom action research and the data were described quantitatively. The data of this study were collected through the observation and students’ final score, observation was used to analyze the percentage of teacher activity in the class while the students’ final score was aided to know the students’ improvement. The research subjects were the fifth graders of elementary Sedenganmijen, Krian, Sidoarjo. The result of the study showed that there was a significant improvement, in the first circle the percentage of successful students was 68% while in the second circle the percentage was improved to 92%. It can be concluded that the learning process using Puzzle two dimensien space media could improve the students’ achievement in the learning material of identification of characteristics of two dimensien in the elementary school.